Click modified amphiphilic graft copolymeric micelles of poly(styrene-alt-maleic anhydride) for combinatorial delivery of doxorubicin and plk-1 siRNA in cancer therapy. Issue 45 (2nd November 2016) - Aji Alex, M. R.; Veeranarayanan, Srivani; Poulose, Aby Cheruvathoor; Nehate, Chetan; Kumar, D. Sakthi; Koul, Veena
Abstract : Co-delivery of drug and siRNA using cationic polymeric micelles. Abstract : The anti-apoptotic defense mechanism of cancer cells poses a major hurdle which makes chemotherapy less effective. Combinatorial delivery of drugs and siRNAs targeting anti-apoptotic proteins is a vital means for improving therapeutic effects. The present study aims at designing a suitable carrier which can effectively co-deliver doxorubicin and plk1 siRNA to tumor cells. Low molecular weight poly(styrene- alt -maleic anhydride) was chemically modified via a click reaction to obtain a cationic amphiphilic polymer for the co-delivery of therapeutic agents. Short glycol chains were utilized as linker molecules for grafting which in turn imparted a stealth nature and minimized plasma protein adsorption to the polymeric surface. Isonicotinic acid was grafted to the polymer due to its ability to penetrate the endolysosomal membrane and arginine–lysine conjugates were embedded for complexing siRNA. The polymer was able to self-assemble in to smooth, spherical micellar structures with a CMC of ∼3 μg mL −1 . The particle size of the micelles was ∼14–30 nm as depicted using TEM and FESEM. Atomic force microscopic analysis showed an average height of ∼12 nm for the polymeric micelles. An optimum doxorubicin loading of ∼9% w/w was achieved with the micelles using a dialysis method. Effective complexation of siRNA occurred above a polymer/siRNA weight ratio of 10 without any significant change in the particle size. Doxorubicin and fluorescent labeled siRNA loaded micelles exhibited excellent co-localization within the cytoplasm of MCF-7 cells. The synergistic effect of the active agents in inhibiting tumor cell proliferation was depicted using an MTT assay and visualized using calcein/propidium iodide staining of the treated cells. Co-administration of doxorubicin and plk1 siRNA in EAT tumor bearing Swiss albino mice using the cationic micelles significantly enhanced the antitumor efficacy.